PENGARUH KINERJA KEUANGAN DAERAH PADA PERTUMBUHAN EKONOMI DAN PENGANGGURAN DI PROVINSI NUSA TENGGARA TIMUR - Yuniarti Reny Renggo (Jurnal Ekonomi-Qu, 2021)
The ability to manage regional finances is seen from the performance of regional finances, where regional financial performance can be an indicator to measure the success of the region in implementing regional autonomy. This study aims to see the effect of regional financial performance on economic growth and unemployment in East Nusa Tenggara Province from 2016 to 2019. Using panel data regression analysis and indicators of financial performance, among others, independence ratios, effectiveness ratios and efficiency ratios. The results obtained in this study are, the independence ratio is classified as low criteria with a consultative relationship pattern does not have a significant effect on economic growth and the unemployment rate, the effectiveness ratio is classified as very effective but does not have a significant effect on economic growth and the unemployment rate, while the efficiency ratio is classified as quite efficient significantly reduce economic growth but not the unemployment rate.